1998
DOI: 10.1177/108056999806100211
|View full text |Cite
|
Sign up to set email alerts
|

Community Service Learning Increases Communication Skills Across the Business Curriculum

Abstract: Community service learning offers a unique and rewarding way for business students to reinforce communication capabilities while developing lifelong career and social skills. This article defines community service learning, dis cusses its importance to business as well as higher education, and describes three community service learning projects. Students in these projects taught elementary students, designed a computer system for a community nonprofit, and developed accounting systems for university divisions.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(52 citation statements)
references
References 2 publications
2
47
0
1
Order By: Relevance
“…For example, Tucker et al (1998) and colleagues identified that students in entrepreneurship or strategy classes can make a positive impact on a community organization by using their knowledge to develop business plans for projects to benefit low-income communities. As identified by Ayers et al (2010), this form of community engagement improves a student's professional toolbox as well as provides an opportunity to interact in team settings.…”
Section: Service-learning In Higher Educationmentioning
confidence: 99%
“…For example, Tucker et al (1998) and colleagues identified that students in entrepreneurship or strategy classes can make a positive impact on a community organization by using their knowledge to develop business plans for projects to benefit low-income communities. As identified by Ayers et al (2010), this form of community engagement improves a student's professional toolbox as well as provides an opportunity to interact in team settings.…”
Section: Service-learning In Higher Educationmentioning
confidence: 99%
“…Community service learning and service learning also enable students to develop a number of their skills. Thanks to community service activities, students improves their skills in such subjects as team work, leadership, conflict resolution, communication and time management (Tucker, McCarthy, Hoxmeier and Lenk, 1998). At the same time, in such process these students can also form their awareness of being able to evaluate their own perfection and features.…”
Section: Discussion Results and Suggestionsmentioning
confidence: 99%
“…Educators, researchers, and policy makers believe that community service activities provide valuable experiences and learning environment for students (Nathan and Kielsmeier, 1991; cited by Shiarella, Mccarthy and Tucker [42]). In the form of service-learning, community service presents an opportunity for students to improve numerous skills, including team building, leadership, conflict resolution, communication, organization, and time management (Tucker, McCarthy, Hoxmeier and Lenk, 1998).…”
Section: A Pattern For Metacognitive Awareness and Community Service mentioning
confidence: 99%
“…In spite of the many promises that service-learning offers, studies have found mixed results (Tucker, McCarthy, Hoxmeier, & Lenk, 1998). A recent study found that design, implementation and sustainability of service-learning.…”
Section: Students' Community Awarenessmentioning
confidence: 99%